Fish diseases and medicine - Smith, Stephen A., 1954- (Boca Raton, Florida : CRC Press, 2019)
Fish are critically importantto the welfare of this planet and its occupants,the health of both wild and captive fish populations paramount toour survival. This book presentsthe gross pathology of the most commonly encountered diseases and syndromes of fish in an organ system-based approach. It provides an overview of the di
11. HEPATIC, BILIARY, AND PANCREATIC DISEASESEpizootic hematopoietic necrosis; Hepatic lipidosis; Infectious pancreatic necrosis; Mycobacteriosis and nocardiosis; Microcystins and net pen liver disease; Neoplasia; Pancreas disease/sleeping disease; Parasites; Pasteurellosis (Photobacteria damselae ssp. piscicida); Salmon rickettsial septicemia; References; 12. RENAL DISEASES AND DISORDERS; Bacterial Kidney Disease; Enteric Septicemia of Catfish; Piscirickettsiosis; Francisellosis; Mycobacteriosis; Proliferative Kidney Disease; Kidney Enlargement Disease of Goldfish; Acolpenteron Ureteroecetes
Includes bibliographical references and index.
Description based on print version record.
Keywords: Fishes -- Diseases; Enfermedades de los peces